IMPLEMENTATION OF COUNSELLING GUIDANCE PROGRAM IN INFORMATION SERVICES TO IMPROVING DISCIPLINARY - Syafaruddin Syafaruddin; Edi Saputra; Muhammad Zakiuddin (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2019)
The results of this study are (1)Guidance and counseling programs implemented at MAN 1 Medan, namely guidance andcounseling programs that are truly in accordance with the implementation of guidance andcounseling services in general. The guidance and counseling program consists of annual,semester, monthly, weekly and daily programs. Preparation of this guidance and counselingservice program to meet the targets or objectives of the implementation of guidance andcounseling services. (2) The implementation of information services in fostering discipline inMAN 1 Medan students by providing information including how to divide time, arrange aschedule of learning activities, how to learn effectively, how to choose learning techniques,and information about learning discipline. (3) Information services play a role in improvingstudent discipline, that is, students are able to absorb social knowledge and understanding indepth towards themselves.